Pengaruh Rasio Keuangan Terhadap Pertumbuhan Laba Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Happy, Adita; Dwi Warsitasari, Wahyu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to collect data that demonstrates how various financial ratios affect the development of a company's bottom line. Multiple ratios are used in the analysis, such as the Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TAT), and Net Profit Margin (NPM). This research covers the time period from 2017 to 2021 and is limited to manufacturing companies that are listed on the Indonesia Stock Exchange. Eight of these organizations make up the sample size for this study. The f-test and t-test are used to examine the hypotheses, and the multiple linear regression analysis model is used for data analysis in this study. This investigation suggests that neither the Current Ratio (CR), nor the Debt to Equity Ratio (DER), nor the Total Asset Turnover (TAT) significantly affects the development of profits. However, the Net Profit Margin (NPM) is found to be a highly important predictor of future profits. Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TAT), and Net Profit Margin (NPM) were used as independent variables in this investigation.